Enhancement of Photoconductive Detector Based on Carbon Nanotubes Decorated with Silver Nanoparticles by Adding Conductive Polymer - Yousif, Taqwa; Naje, Asama (Iraqi Journal of Physics, 2021)
In this work, wide band range photo detector operating in UV, Visible and IR was fabricated using carbon nanotubes (MWCNTs, SWCNTs) decorated with silver nanoparticles (Ag NPs). Silicon was used as a substrate to deposited CNTs/Ag NPs by the drop casting technique. Polyamide nylon polymer was used to coat CNTs/Ag NPs to enhance the photo-response of the detector. The electro-exploding wire technology was used to synthesize Ag NPs. Good dispersion of silver NPs achieved by a simple chemistry process on the surface of CNTs. The optical, structure and electrical characteristic of CNTs decorated with Ag NPs were characterized by X-Ray diffraction and Field Emission Scanning Electron Microscopy.  X-ray diffraction patterns of Ag NPs exhibited 2θ values (38.1°,44.3°) corresponding to the Ag nanocrystal, while the XRD pattern of MWCNTs and SWCNTs /Ag NPs peaks appeared at 2θ = 26.2° corresponding to the (002) and at 2theta=44° which corresponds with miller indices (100) for CNTs and (200) for Ag NPs. The optical properties measured by UV-Vis. Spectroscopy. Broad and strong surface plasmon resonance (SPR) peak was detected at 420 nm, for Ag NPs. The absorption of CNTs/Ag NPs increased significantly from UV to near IR region (300-1000 nm).  Ag NPs decorated CNTs without any impurities, according to field mission scanning electron microscopy examination, with typical particle sizes of (50-80nm) for Ag-NPs, 44nm for MWCNTs/Ag-NPs, and 30nm for SWCNTs/Ag NPs. ֹThe I-V characteristics at forward bias voltage (0.5-10) volt were studied. The figure of merits (responsivity, photocurrent gain, NEP and detectivity) after coating with polymer of the detector were measured in the dark and after illumination with UV LED (365 nm), Tungsten lamp (500-800 nm) and Laser diode (808 nm).